Evolution of Individual’s Intellect as Basis for Forming Intellectual Capital of Organization - NEDOLUZHKO, Olga V.; VARKULEVICH, Tatyana V.; BATURINA, Olga A. (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
The article stipulates the reasonability to study intellectual capital of the organization as the one that is complicated in the process of evolution. It describes the evolutionary model of intellectual capital as a succession of types of activity that provides its creation. On the basis of using the analog method, the scheme of evolution of types of individual’s intellect is correlated with the types of organizational activity performed with their aid. Intellectual capital of organizations is represented as an informational system that reflects its development as acquisition of new qualitative characteristics by it. It allows singling out types of organizational activity in relation to and peculiar of a specific organization. Using categorical and system methodology in particular ‘Final Information Flow’ method, a more complete and accurate description of intellectual capital in the form of qualitative characteristics was received. The latter determine the possibility to perform various types of activity by the organization that lead to the creation of intellectual capital and combination of these types. Purposeful searching for qualitative characteristics of the object expressed as a set of parameters of the categorical model allowed to define the succession of performing various types of the organizational activity. It provides the possibility to identify the level of the formed intellectual capital of a specific organization, and to reveal the potential and conditions of its further efficient use.